Comparison of annual biosynthetic calorie productions by phytoplankton in different southern Korean bays - Jang, Hyo Keun; Kang, Jae Joong; Lee, Jae Hyung; Lee, Dabin; Jo, Naeun; Kim, Yejin; Kim, Kwanwoo; Kim, Myung-Joon; Park, Sanghoon; Kim, Jaehong; Kim, Jaesoon; Ahn, So Hyun; et al. (Frontiers in Marine Science, 2024)
We investigated assessments of calorie production and energy efficiencies of phytoplankton in Gwangyang, Jaran, and Geoje-Hansan bays in southern Korea, based on seasonal field measurements data for particulate organic carbon (POC), macromolecular compositions, calorie contents, and primary production. Our findings revealed that Geoje-Hansan Bay consistently exhibits higher POC concentrations compared to Gwangyang and Jaran bays, except during the summer season. The observed seasonal variations in POC concentrations and primary productions indicated distinct factors influencing POC distribution among the bays, which varies with the seasons. Macromolecular compositions displayed notable patterns, with Gwangyang Bay exhibiting pronounced seasonal variations, Jaran and Geoje-Hansan bays showing stable carbohydrate (CHO) dominance, and Gwangyang Bay displaying protein (PRT) dominance influenced by river-borne nutrients. Analysis of calorie content revealed that Geoje-Hansan Bay exhibited the highest calorie content, suggesting a more favorable physiological state of phytoplankton compared to Gwangyang and Jaran bays. Estimations of annual primary production and calorie production demonstrated regional variations, with Geoje-Hansan Bay having the highest values followed by Jaran Bay and Gwangyang Bay. These differences in primary production and calorie production reflect the diverse ecological conditions and nutrient availability specific to each bay. Interestingly, Gwangyang Bay demonstrated the highest energy efficiency, producing more calories per unit of carbon compared to the other two bays, potentially due to the influence of different dominant phytoplankton communities. This study enhances our understanding of ecosystem dynamics and ecological characteristics among the three bays, emphasizing the importance of considering seasonal variations and specific bay characteristics in investigating biogeochemical processes, energy flow, and ecosystem functioning. The findings contribute valuable insights for the sustainable management of coastal ecosystems and aquaculture practices.